Towards the Development of Competency Areas for Student Affairs and Services Administrators: Perspectives for Professionalization - Caranto, Melfi M. (Universiti Sains Malaysia, 2016)
The research is concerned primarily with establishing a set of competency areas for administrators of student affairs and services in the Philippines regardless of their area of specialization or positional role within the field. A total of twenty (20) representatives from major regions of the country participated in the study. The modified Delphi method was adopted as the process of obtaining data. There were nine competency areas presented, namely: Advising and Helping; Assessment; Evaluation, and Research; Equity, Diversity, and Inclusion; Ethical Professional Practice; Human and Organizational Resources; Law, Policy, and Governance; Leadership; Personal Foundations; and Student Learning and Development. It was found that: (1) the competency areas mentioned were relevant regardless of educational background, number of years in service, position or job designation, organization affiliation and type of school where they were working; (2) the competency areas presented were acknowledged and perceived to be most important and/or greatly important by administrators and practitioners of Student Affairs and Services; and (3) the identified competency areas may serve as guidelines for student affairs and services administrators toward the development of the profession.